Therapeutic Efficacy and Neurobiological Mechanisms of Nitrous Oxide in Treatment-Resistant Depression: Review Article (Journal of Pharma Insights and Research, 2025)
Major Depressive Disorder (MDD), particularly its treatment-resistant form, represents a substantial burden on global public health, characterized by low remission rates with conventional monoaminergic pharmacotherapy. The paradigm shift toward glutamatergic modulation has identified the N-methyl-D-aspartate (NMDA) receptor as a critical target for rapid-acting antidepressants. Nitrous oxide (N2O), an inhalational anesthetic utilized safely in medicine for nearly two centuries, has emerged as a potent antagonist of the NMDA receptor with demonstrated efficacy in ameliorating depressive symptoms. Accumulating evidence indicates that a single inhalation session can yield rapid antidepressant effects lasting significantly longer than the pharmacokinetic elimination of the gas. While early investigations utilized psychotomimetic concentrations comparable to anesthetic induction, recent dose-finding studies suggest that sub-anesthetic concentrations, specifically 25%, offer a favorable therapeutic index by maintaining antidepressant efficacy while significantly minimizing adverse effects such as nausea and dissociation. Beyond NMDA antagonism, the mechanism of action appears to involve complex interplay with the endogenous opioid system, GABAergic disinhibition, and downstream neuroplasticity signaling pathways, including Brain-Derived Neurotrophic Factor (BDNF) release. Current research prioritizes establishing optimal dosing protocols, mitigating risks associated with vitamin B12 oxidation, and determining the feasibility of nitrous oxide as a scalable, office-based intervention. The translation of this anesthetic agent into a psychiatric tool requires rigorous standardization of delivery methods and strict vigilance regarding metabolic contraindications